Temperature sensitivity of Cu K-alpha imaging efficiency using a spherical Bragg reflecting crystal - Akli, K; Key, M; Chung, H; Hansen, S; Freeman, R; Chen, M; Gregori, G; Hatchett, S; Hey, D; Izumi, N; King, J; Kuba, J; et al. (2007)
The interaction of a 75 J 10 ps, high intensity laser beam with low-mass, solid Cu targets is investigated. Two instruments were fielded as diagnostics of Cu K -shell emission from the targets: a single photon counting spectrometer provided the absolute Kα yield [C. Stoeckl, Rev. Sci. Instrum. 75, 3705 (2004)] and a spherically bent Bragg crystal recorded 2D monochromatic images with a spatial resolution of 10 μm [J. A. Koch, Rev. Sci. Instrum. 74, 2130 (2003)]. Due to the shifting and broadening of the Kα spectral lines with increasing temperature, there is a temperature dependence of the crystal collection efficiency. This affects measurements of the spatial pattern of electron transport, and it provides a temperature diagnostic when cross calibrated against the single photon counting spectrometer. The experimental data showing changing collection efficiency are presented. The results are discussed in light of modeling of the temperature-dependent spectrum of Cu K -shell emission. © 2007 American Institute of Physics.